2016
DOI: 10.1113/jp272942
|View full text |Cite
|
Sign up to set email alerts
|

Distinct subcellular mechanisms for the enhancement of the surface membrane expression of SK2 channel by its interacting proteins, α‐actinin2 and filamin A

Abstract: The normal function of ion channels depends critically on the precise subcellular localization and the number of channel proteins on the cell surface membrane. Small-conductance, Ca -activated K channels (SK, K 2) are expressed in human atrial myocytes and are responsible for shaping atrial action potentials. Understanding the mechanisms of SK channel trafficking may provide new insights into the regulation controlling the repolarization of atrial myocytes. We have previously demonstrated that the C- and N-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…; Zhang et al . ). It is possible that differential channel trafficking properties exist between sexes and contribute to different I KAS responses to sympathetic stimulation.…”
Section: Discussionmentioning
confidence: 97%
“…; Zhang et al . ). It is possible that differential channel trafficking properties exist between sexes and contribute to different I KAS responses to sympathetic stimulation.…”
Section: Discussionmentioning
confidence: 97%
“…Negative controls with secondary antibodies alone were performed for all experiments. For testing the SK2 antibody, Human Embryonic Kidney (HEK) 293 cells were cultured and transfected by human cardiac SK2 plasmid using the similar methods we reported before 32 .…”
Section: Methodsmentioning
confidence: 99%
“…SK2 channels directly interact with α-actinin2 and MLC2 via their C-termini and with filamin A via their N-termini 26 . New insights into the regulation controlling the repolarization of the atrial myocytes have demonstrated that α-actinin2 facilitates the recycling of SK2 channels from both early and late endosomes, while filamin A likely assists in the recycling of SK2 channels from recycling endosomes 27 .…”
Section: Structure and Function Of Sk Channels In The Heartmentioning
confidence: 99%